Life Cycle in the Beliefs of the Atoni Pah Meto People - Hawu Haba, Yuda D.; Djawa, Maya; Saingo, Yakobus Adi (JURNAL LEDALERO, 2025)
Cultural diversity in Indonesia acts as a catalyst for tolerance and the formation of a diverse society with values rooted in religion, local wisdom, and cultural heritage. However, the low level of spiritual understanding and inadequate cultural integration in East Nusa Tenggara have triggered the emergence of cases that disregard the human life cycle, such as the prevalence of abortion and suicide, as well as social and economic pressures that undermine the mental well-being of the community. Previous research delved into the local wisdom of the Timorese community, the historical aspects of the Timorese culture, and the Toit Ulan Ritual in Central Amanuban. This study focuses on the beliefs of Atoni Pah Meto in the Banamas Neonsaet (East Amanuban), exploring its cultural heritage and local beliefs. It aims to understand the impact of ceremonies on each life stage from the perspective of their local wisdom that contributing to the preservation of the community’s mental well-being. Utilizing qualitative methods and a phenomenological approach involving community leaders, the study employs observation, interviews, and documentation, with subsequent data reduction, presentation, and verification. Findings highlight that life-cycle ceremonies reflect values of familial bonds, cooperation, and harmony with nature. Marriage and funeral processes involve family roles in maintaining spirituality and warding off spiritual disturbances. Despite the influence of formal religion, traces of traditional beliefs persist, shaping a unique identity that harmonizes cultural heritage and religion. The research underscores the importance of preserving and understanding this cultural richness for the sustainability and harmony of the Atoni Pah Meto in the East Amanuban. Key words: East Amanuban, Ceremony, Life Cycle, Local Wisdom, Atoni Pah Meto.